Factors Influencing Job Satisfaction in Insurance Employees PT. Starinvestama - Nor Lailla; M. Irfan Tarmizi; Intan Rizkia Chudric (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
Job satisfaction (JS) is satisfaction with work. It is considered a concept that describes work behavior, especially in the insurance sector which is one of the sectors that provides financial services. The purpose of this study was to determine: The effect of proactive personality (PP) on intrinsic motivation (IM); the effect of PP on JS; IM on JS; and the effect of PP on JS with IM mediation. The method used in this study is quantitative, with a population of employees of PT. Asuransi Jiwa Starinvestama. The sampling technique in this study was saturated sampling, using the SmartPLS analysis tool. The results of the study showed: there was no effect of PP on IM; there was an effect of PP on JS; there was IM on JS; and there was an effect of PP on JS with IM mediation. The study concludes that the ideas conveyed by employees and employee pleasure in doing work are the main keys to job satisfaction. The implication is that organizations need to enhance intrinsic motivation through job autonomy and support, as a proactive personality alone is not enough. Furthermore, intrinsic motivation has been shown to strengthen the influence of a proactive personality in increasing employee job satisfaction.